2014
DOI: 10.1002/2014jc010100
|View full text |Cite
|
Sign up to set email alerts
|

The influence of salinity on tropical Atlantic instability waves

Abstract: Sea surface salinity (SSS) data derived from the Aquarius/SAC-D satellite mission are analyzed along with other satellite and in situ data to assess Aquarius' capability to detect tropical instability waves (TIWs) and eddies in the tropical Atlantic Ocean and to investigate the influence that SSS has on the variability. Aquarius data show that the magnitude of SSS anomalies associated with the Atlantic TIWs is 60.25 practical salinity unit, which is weaker than those in the Pacific by 50%. In the central equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 63 publications
4
41
0
Order By: Relevance
“…Figure 6b shows the global averages of regional temporal STD values of Aquarius SSS with respect to Argo-SIO SSS for various spatial scales. The difference between Figure 6a [4,21], Madden-Julian Oscillation [22,23], El Niño-Southern Oscillation [24], and Indian Ocean Dipole [25]. It is noteworthy that the global average STD value for non-seasonal SSS anomalies is less than 0.1 psu for 1 • × 1 • scale and 0.04 psu for 10 • × 10 • scale.…”
Section: Quantification Of the Time-mean Seasonal And Non-seasonal mentioning
confidence: 89%
See 1 more Smart Citation
“…Figure 6b shows the global averages of regional temporal STD values of Aquarius SSS with respect to Argo-SIO SSS for various spatial scales. The difference between Figure 6a [4,21], Madden-Julian Oscillation [22,23], El Niño-Southern Oscillation [24], and Indian Ocean Dipole [25]. It is noteworthy that the global average STD value for non-seasonal SSS anomalies is less than 0.1 psu for 1 • × 1 • scale and 0.04 psu for 10 • × 10 • scale.…”
Section: Quantification Of the Time-mean Seasonal And Non-seasonal mentioning
confidence: 89%
“…Figure 6c,d shows the global average of STD values for composite seasonal anomalies and nonseasonal anomalies (referenced to the composite seasonal cycle) of the SSS differences between Aquarius and Argo-SIO. The non-seasonal anomalies are associated with the differences between Aquarius and Argo-SIO in representing non-seasonal signals associated with phenomena such as tropical instability waves [4,21], Madden-Julian Oscillation [22,23], El Niño-Southern Oscillation [24], and Indian Ocean Dipole [25]. It is noteworthy that the global average STD value for non-seasonal SSS anomalies is less than 0.1 psu for 1° × 1° scale and 0.04 psu for 10° × 10° scale.…”
Section: Quantification Of the Time-mean Seasonal And Non-seasonal mentioning
confidence: 99%
“…The spatial pattern of the remaining variance closely resembles the total SSS variability: values up to 0.5 g/kg at the sea ice edge in the Nordic seas and Labrador Sea; also comparably large values north of the Gulf Stream and somewhat larger values (up to 0.7 g/kg) at the mouth of the Amazon River and at the exit of the Baltic Sea. Along the equator, values of up to 0.4 g/kg (confirmed by the independent results at the mooring stations) partly reflect the influence of the tropical instability waves with periods of 20–40 days [ von Schuckmann et al ., ; Lee et al ., ]. These are regions where large‐amplitude fast processes make observing SSS challenging.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Satellite measurements offer the opportunity to observe the SSS with an unprecedented resolution about 50–150 km, 3–7 days [ Lee et al ., ; Hernandez et al ., ; Reul et al ., ; Lu et al ., ]. In the tropical Atlantic, satellite observations allow to monitor the seasonal SSS variability [ Tzortzi et al ., ] and to detect tropical instability waves (TIWs) [ Lee et al ., ]. Lee et al .…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al . [] showed that SSS horizontal gradient significantly contributes to the dynamical balance of TIWs by enhancing the meridional density gradient in the tropical Atlantic, especially during boreal spring.…”
Section: Introductionmentioning
confidence: 99%